Geophysical field theory and method. - Kaufman, Alexander A., 1931-2023 (International geophysics series, 1992)
An essential book for all students and scientists in the field, Part A of Geophysical Field Theory and Method describes the physical and mathematical principles of geophysical methods, specifically the behavior of gravitational, electrical, and magnetic fields. The broader use of these methods underlines the far-reaching appeal of this book. Oil and mineral prospecting, solving groundwater and engineering problems, and well-logging are just some of the activities which involve geophysical methods.